#### Answer

$3x-10$

#### Work Step by Step

Subtract each term of the subtrahend to obtain:
$(2x-7)-(3-x)
\\=2x-7-3-(-x)
\\=2x-7-3+x$
Combine like terms to obtain:
$=(2x+x)+(-7-3)
\\=3x+(-10)
\\=3x-10$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$3x-10$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.